Digital Readiness of PAI Students at Universitas Ahmad Dahlan for the Integration of Artificial Intelligence in Islamic Values-Based Learning - Restu Nandayu; Arif Rahman (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The swift advancement of Artificial Intelligence (AI) has significantly impacted higher education, encompassing Islamic Religious Education (PAI). This research intends to evaluate the preparedness of Islamic Religious Education students at Universitas Ahmad Dahlan regarding the incorporation of Artificial Intelligence into learning based on Islamic principles. An explanatory sequential mixed-methods approach was utilized in this investigation, which comprised both quantitative and qualitative stages. The quantitative portion involved the collection of data via structured online questionnaires distributed to 109 currently enrolled PAI students, while qualitative insights were gathered through semi-structured interviews with chosen individuals to elaborate on the quantitative results. The quantitative data were examined using descriptive statistical methods (including frequency, percentage, and mean score), whereas the qualitative data underwent thematic analysis. The results indicate that students demonstrate relatively high digital readiness, particularly in technical competence and positive perceptions of AI. Ethical awareness toward AI utilization based on Islamic values also shows a high level, while adaptive readiness and critical AI literacy still require improvement. The qualitative findings reveal that Islamic values, institutional support, and lecturer guidance strengthen students' responsible use of AI in learning. This study concludes that successful AI integration in Islamic education requires not only technological competence but also ethical awareness and institutional support aligned with Islamic values.